ANALISIS EFISIENSI SISTEM PEMBAYARAN MANUAL DAN DIGITAL DI RUMAH SAKIT - Susanti, Ai Susi; Dewi, Kurnia (Jurnal Manajemen Kesehatan Indonesia, 2025)
This study aims to compare and assess the efficiency of manual and digital payment methods used by hospital cashiers. The shift towards digitization in health service administration, has become more relevant due to the demand for faster, more accurate, and transparent transactions. This descriptive quantitative study used primary data on the average length of transactions as well as secondary data on the number of transactions per month at RSAU dr. M. Salamun Hospital in the months of March and April. In addition to a 40-second time saving compared to cash transactions, the results demonstrated that digital payments processed using QRIS have the potential to streamline services by reducing wait times, particulary during peak periods. QRIS usage increased during the two months under study, despite cash’s continued dominance. Full adoption is hampered, nevertheless, particularly in the pharmacy unit where there are issues with tax integration and insufficient corporate procedures. Both staff and younger patients reported that they favored digital methods since they were quick and easy, while elderly patients opted to stick with cash. The results of the study show that QRIS offers a more effective alternative. Nonetheless, wider implementation of QRIS requires technology integration and policy alignment. Future research should look at the effects of digital technologies on patient satisfaction and workflow optimization across various hospital departments.